A sample based membership analysis of sports clubs in Slovenia - Šugman, Rajko (Kinesiologia Slovenica, 2003)
The article is based on the study 'A sample analysis of the number and structure of membership in grassroots sports organisations in individual sports disciplines in Slovenia' (Šugman, 1999a). We classified 14 socio-demographic variables among basic variables that enabled us to identify the membership of sports associations and clubs and which functions individual members hold through their activities. We collected the principal information by way of a survey carried out in the period 1 February 1998 to 1 March 1999. All together, we sent out 1,130 survey questionnaires. We received answers from 737 associations involved in 51 sports disciplines, meaning a response rate of 65.2 percent. The results reveal the big difference in the scope and structure of Slovenian sports clubs. On one hand, we have some clubs with just 10 members and, on the other, clubs with three thousand members. Approximately 40% of clubs included categorised athletes among their members. The study thoroughly analyses coaches, particularly professional ones and those with amateur-level skills. We also noticed at least one referee, one organisational and one technical worker in about 60% of clubs depending on the siye of membership and the number of categorised athletes. The articlećs aim is to outline the characteristics of the following association and club members, about whom we know very little: referees, technical delegates, organisational and technical workers.
Keywords: kadrovska politika; kultura športa; organiziranost; raziskave; struktura; šport; športna društva; športne organizacije; športne panoge